Women In Gender (Critical Discourse Analysis on Novel I am Malala by Malala Yousafzai and Christina Lamb) - Syamsiah, Nur (English Education: Jurnal Tadris Bahasa Inggris, 2016)
The purpose of this study was to describe how the text of gender-based violence against the woman, and illustrate how gender-based injustice is run and produced in the Novel I am Malala, through the texts that have been written. This study used a qualitative descriptive of critical perspective (Genre of Critical Theory), perspective/paradigm used to explain the description of gender-based violence (violence against women) in the novel I am Malala. Data analysis technique this study is Critical Discourse Analysis of Norman Fairclough (Texts Analysis, Discourse Analysis sociocultural Practice and Practice). The result in this study is the violence and gender-based injustice or inequality of women presented in the novel I am Malala.